Early childcare enrollment and the pursuit of higher education: A Canadian longitudinal study. (August 2022) - Garon-Carrier, Gabrielle; Ansari, Arya; Letarte, Marie-Josée; Fitzpatrick, Caroline
Abstract: This study examined the associations between childcare attendance among 550 children from 24 to 36 months of age and their enrollment in higher education in young adulthood. We conducted a propensity score matching analysis to control the selection bias for childcare attendance and estimated the average treatment effect for the treated on the odds of enrollment in higher education. Children who attended informal childcare (i.e., with a relative or nanny) were more likely to pursue higher education in young adulthood relative to children in formal childcare (i.e., center-based or licensed home-based childcare). However, heterogeneity in our sample revealed that attending formal childcare increased the probability of enrollment in higher education for children from low-income and non-employed families. This study suggests that attending informal childcare in Canada in 1994–1995 benefited all children over 20 years later, whereas attending formal childcare appears to be protective for children from more disadvantaged families. Highlights: Early childcare attendance predicts the pursuit of higher education. Informal care increased the probability of pursuing higher education for all children. Formal care increased the probability only for low-income and non-employed families.